(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The article analyses Rosmini’s critique of Kant’s philosophy. The author aludes to the criticism of Kant as a question of principles that criticizes Kant’s subjectivism and the wrong formulation of the ideological problem (of the origin of ideas) related to the synthetic a priori judgments. Ending by holding that Kant confuses predicates with attributes, concepts with things, and leads his philosophy to subjectivism.